2005
DOI: 10.1253/circj.69.1521
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Phase Images in Fourier Analysis Using Gated Cardiac POOL-SPECT for Determining the Indication for Cardiac Resynchronization Therapy

Abstract: ntraventricular conduction delay is clearly found in some patients with heart failure and these conduction abnormalities might be related to a delay in the onset of right or left ventricular (LV) contraction. Inefficient cardiac contraction caused by such mechanical asynchrony may be partly responsible for further impairment of LV function. Cardiac resynchronization therapy (CRT) restores optimum synchrony of ventricular contraction. A metaanalysis of 4 randomized controlled trials showed that the morbidity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
0
12
0
2
Order By: Relevance
“…Also computed were ''z-scores,'' defined conventionally as the difference between a measurement for an individual versus the mean for a normal population, and normalized to the standard deviation for a normal population, for which values [2.0 indicate a probability [95% for the measured parameter to fall outside the normal range [15]. RV-LV apical phase differences also were computed [9].…”
Section: Regional Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Also computed were ''z-scores,'' defined conventionally as the difference between a measurement for an individual versus the mean for a normal population, and normalized to the standard deviation for a normal population, for which values [2.0 indicate a probability [95% for the measured parameter to fall outside the normal range [15]. RV-LV apical phase differences also were computed [9].…”
Section: Regional Parametersmentioning
confidence: 99%
“…GBPS has been used to quantify regional function as well as global function [6,8]. GBPS measurements have shown that clinical improvement of patients with dilated cardiomyopathy following successful CRT is accompanied by improved intra-and inter-ventricular synchrony [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 As for the latter, several recent reports have suggested that selection based on the direct assessment of mechanical dyssynchrony by tissue-Doppler echocardiography is a potentially useful tool to increase response rate for CRT. [12][13][14][15][16][17] As for the optimal LV pacing site, the PATH-CHF II study has demonstrated that pacing at LV free wall sites consistently produces better short-term hemodynamic responses than does pacing at LV anterior sites. 4,5 Furthermore, Auricchio et al demonstrated that the functional block line of LV, as determined by CARTO and non-contact mapping, varied among individual patients with left bundle branch block (LBBB) (ie, anterior, lateral, or inferior aspects), and suggested that the site of delay above the functional block line was the optimal pacing site.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with computed tomography by single photon emission are being developed, which can improve the performance of this technique in evaluating dyssynchrony and help to determine the implantation site of the electrode in LV 34 . On the other hand, determination of normal values for specific groups, e.g.…”
Section: Discussionmentioning
confidence: 99%